The Effect of the Ratio of Beetroot Juice with Pineapple Juice and Gelatine Addition on the Characteristics of Jelly Candy - Desi Revina Amy Naibaho; Rona J. Nainggolan; Elisa Julianti (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The aim of the research was to find the effect of the ratio of beetroot juice and pineapple juice with addition of gelatine on the characteristics of  jelly candy. The research was done by using completely randomized design with two factors, i.e the ratio of beetroot juice and pineapple juice(S): (10%:90%, 20%:80%, 30%:70%, 40%:60%) and gelatine addition (G): (4%, 5%, 6%). The analyzed parameters were moisture content, ash content, vitamin C content, total acid, total soluble solid and sensory test (color, flavor, taste, and texture). The result showed that the ratio of beetroot juice with pineapple juice had highly significant effect on  ash content, vitamin C content, total acid, total soluble solid, and sensory test (color, flavor, and taste). Gelatine addition had highly significant effect on moisture content, ash content, vitamin C content, total acid, total soluble solid, and sensory test texture (hedonic). The Interaction between the ratio of beetroot juice with pineapple juice and gelatine’s concentration gave highly significant effect on ash content and signigicant effect on sensory test of color. The ratio of the beetroot juice with pineapple juice of 30%:70% (S3) and gelatine’s concentration of 4% (G1) produced the best jelly candy product. For the best product antioxidant activity was determined. Keywords: Beetroot juice, gelatin, jelly candy, pineapple juice.